Cation Exchange Equilibrium and Affinity Studies of Some Lanthanides(III) in Isopropanol Solvents - Bharadwaj, Archana; Bharadwaj, S.D. (Asian Journal of Chemistry, 2010)
Studies of cation exchange equilibrium and affinity of some lighter lanthanides e.g., lanthanum, cerium, praseodymium, neodymium and samarium ions in isopropanol solvents. Equili-brium exchanges studies were carried at room temperature in this way for La3+, Ce3+, Pr3+, Nd3+ and Sm3+ ions of three (0.1, 0.05 and 0.025 N) ionic concentration in aqueous isopropanol solvents and containing 10, 20, 30, 40 and 50 % (v/v) isopropanol and by using cation exchanges IC NAC-C-267, having 5.7 meg capacity and 40-60 mesh resin size.